Organized Crime - Prostitution in Bosnia and Herzegovina (Kriminalističke teme, 2003)
Human Trafficking and Illegal Migration are a growing problem for Bosnia & Herzegovina (BiH) and its surrounding neighbors. It affects borders and economies, and its connection to organized crime threatens the integrity of our criminal Justice systems and even stability of our nations by fostering widespread corruption. In fact, it is a global problem that affects us all. Laura Neubauer (USA)The prostitution is widely spread in the whole territory of BiH. In connection with that problematic, female citizens of Eastem- European countries (Russia Ukraine, Moldavia and Romania) is expressed, especially. This work is trying to investigate many questions and give a lot of information in order to comprehend complexity of the problem. For this purpose, a research about the prostitution was done among citizens of Bosnia and HerzegovinaThe results and the conclusions which were made, author will present with this article.